The impact of weather variation on energy consumption in residential houses. - Fikru, Mahelet G.; Gautier, Luis (Elsevier, 2015)
This paper studies the impact of weather variation on energy use by using 5-minutes interval weather–energy data obtained from two residential houses: house 1 is a conventional house with advanced efficiency features and house 2 is a net-zero solar house with relatively more advanced efficiency features. Our result suggests that energy consumption in house 2 is not as sensitive to changes in weather variables as the conventional house. On average, we find that a one unit increase in heating and cooling degree minutes increases energy use by about 9% and 5% respectively for house 1 and 5% and 4% respectively for house 2. In addition, our findings suggest that non-temperature variables such as solar radiation and humidity affect energy use where the sensitivity rates for house 2 are consistently lower than that of house 1. Furthermore our result suggests that the sensitivity of energy use to weather depends on the season and specific time of the day/night.
Keywords: Recursos energéticos renovables; Cambios climáticos; Consumo de energía; Energy consumption; Solar radiation; Solar energy; Case study; Intraday-variation; Texas climate